CAN THE GAMBIA ECONOMY CATCH-UP WITH DEVELOPED ECONOMIES IN THE LONG-RUN?: A Time-Series Test of the Convergence Hypothesis and Endogenous Growth Model with Human Capital - Ayeni, R. K. (Archives of Business Research, 2019)
This paper seeks to answer the question of how The Gambia economy can catch-up with developed economies. The convergence hypothesis implied by the Solow-type (1956) neoclassical model has been questioned by endogenous growth theories mainly in the context of a long-run growth path. One concept says convergence applies if poor economies tend to grow faster than the rich ones so that the poor tend to catch-up with the rich in terms of the level of per capita income. A recent research conducted by the Education Global Practice of The World Bank Group on the public expenditure review (PER) in the education sector in The Gambia made many recommendations on improving human capital development in the Gambia that need empirical clarifications. This paper provides an empirical and theoretical support and justification for the implementation of the recommendations. The paper conducted test of the convergence hypothesis using a series of Cobb-Douglas production models on Gambia using the U.S. economy as the base economy. Time series data on real GDP, Capital stock. Human capital stock and labor were collected for the period 1970 to 2016. The study employed the classical least square regression after establishing the levels of integration of the variables. The study was able to establish that the Gambia economy has the tendency of “catch-up” with developed economy under the condition of improved and sustained human capital development. To achieve this, the paper lends credence to the recommendations of the PER that education budget should be increased in the medium to long term. Convergence may be observed for Gambia economies if it intensifies on subsidies for education, research and development.